Determination of Pralsetinib in Human Plasma and Cerebrospinal Fluid for Therapeutic Drug Monitoring by Ultra-performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS/MS) - Zhao, Zichen; Pu, Qianlun; Sun, Tonglin; Huang, Qian; Tong, Liping; Fan, Ting; Kang, Jingyue; Chen, Yuhong; Zhang, Yan (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background: Ultra-performance Liquid Chromatography-tandem Mass Spectrometry (UPLC-MS/MS) is widely used for concentration detection of many Tyrosine Kinase Inhibitors (TKIs), including afatinib, crizotinib, and osimertinib. In order to analyze whether pralsetinib takes effect in Rearranged during Transfection (RET)-positive patients with central nervous system metastasis, we aimed to develop a method for the detection of pralsetinib concentrations in human plasma and Cerebrospinal Fluid (CSF) by UPLC-MS/MS. Methods: The method was developed using the external standard method, and method validation included precision, accuracy, stability, extraction recovery, and matrix effect. Working solutions were all obtained based on stock solutions of pralsetinib of 1mg/mL. The plasma/CSF samples were precipitated by acetonitrile for protein precipitation and then separated on an ACQUITY UPLC HSS T3 column (2.1×100 mm, 1.8 μm) with a gradient elution using 0.1% formic acid (solution A) and acetonitrile (solution B) as mobile phases at a flow rate of 0.4 mL/min. The tandem mass spectrometry was performed by a triple quadrupole linear ion trap mass spectrometry system (QTRAPTM 6500+) with an electrospray ion (ESI) source and Analyst 1.7.2 data acquisition system. Data were collected in Multiple Reaction Monitoring (MRM) and positive ionization mode. Results: A good linear relationship of pralsetinib in both plasma and CSF was successfully established, and the calibration ranges were found to be 1.0-64.0 μg/mL and 50.0ng/mL-12.8 μg/mL for pralsetinib in the plasma and CSF, respectively. Validation was performed, including calibration assessment, selectivity, precision, accuracy, matrix effect, extraction recovery, and stability, and all results have been found to be acceptable. The method has been successfully applied to pralsetinib concentration detection in a clinical sample, and the concentrations have been found to be 475 ng/mL and 61.55 μg/mL in the CSF and plasma, respectively. Conclusion: We have developed a quick and effective method for concentration detection in both plasma and CSF, and it can be applied for drug monitoring in clinical practice. The method can also provide a reference for further optimization.
Keywords: Pralsetinib